Technical considerations in obtaining platelet rich fibrin for clinical and periodontal research - Vivek Kumar Bains; Jaideep Mahendra; Madhukar Mittal; Muskan Bedi; Little Mahendra (Elsevier, 2023)
Autologous platelet rich fibrin (PRF), is currently being widely used and investigated across the globe by clinicians and periodontal research. The technical aspect required for the procurement of PRF includes revolution per minute (RPM), relative centrifugal force (RCF) or G-force, rotor radius, rotor angle, stability or vibration in the centrifugal machine and material of test-tube, besides the systemic health of the individual may influence the final outcome. Present technical note intends to compile these aspects for better understanding and appropriate outcome while preparing PRF in varying clinical scenarios.